2013
DOI: 10.1097/prs.0b013e3182a48b6c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fat Graft Survival by Bone Marrow–Derived Mesenchymal Stem Cell Therapy

Abstract: Bone marrow-derived mesenchymal stem cells and expanded bone marrow-derived mesenchymal stem cells are capable of improving fat graft survival; bone marrow-derived mesenchymal stem cells are more potent than expanded bone marrow-derived mesenchymal stem cells for doing so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…6 and 7). These observations are also in agreement with the findings of previous studies, demonstrating a link between neovascularization and improved fat graft survival (8,16,35). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…6 and 7). These observations are also in agreement with the findings of previous studies, demonstrating a link between neovascularization and improved fat graft survival (8,16,35). …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Aygit et al (29) revealed that revascularization of fat grafts occurred 48 h post-transplantation, indicating that it is too late for the survival of adipocytes. Various approaches for accelerating angiogenesis have been successfully undertaken to enhance fat survival post-transplantation, including the administration of basic fibroblast growth factors, interleukin-8 and erythropoietin (11,30,31); VEGF-based gene therapy (8,32); and endothelial cell and MSC therapies (13,16,33). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic and Reconstructive Surgery • April 2016 expanded bone marrow-derived mesenchymal stem cells are both beneficial for fat graft survival. 11 However, the bone marrow aspirate and bone marrow concentrate used in this study contain diverse cell contents rather than a single component as in the bone marrow-derived mesenchymal stem cells. Furthermore, harvest is more convenient and timesaving for bone marrow aspirate and bone marrow concentrate than for bone marrow-derived mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11] Even though enhancement of the survival rate has been proved, this technique still possesses potential risks and limitations. The culture and expansion of stem cells are time-consuming and expensive, and the risks of infection and immunologic rejection are increased.…”
mentioning
confidence: 99%